2020
DOI: 10.1371/journal.pone.0234950
|View full text |Cite
|
Sign up to set email alerts
|

How scars shape the neural landscape: Key molecular mediators of TGF-β1’s anti-neuritogenic effects

Abstract: Following injury to the peripheral and central nervous systems, tissue levels of transforming growth factor (TGF)-β1 often increase, which is key for wound healing and scarring. However, active wound regions and scars appear to inhibit process outgrowth by regenerating neurons. We recently showed that corneal wound myofibroblasts block corneal nerve regeneration in vivo, and sensory neurite outgrowth in vitro in a manner that relies critically on TGF-β1. In turn, delayed, abnormal re-innervation contributes to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…As the cells grew toward confluency, they occasionally grew on top of each other in multilayered structures. This is in line with the manufacturer’s description of the cell line and conforms to previous reports in which the cells were cultured on PDL, plastic, or glass surfaces 37 . However, in the L511 and L521 coated wells, the cells continued to grow as monolayers, also toward confluency, which suggests more efficient adhesion to the substrate (Figure 1A).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…As the cells grew toward confluency, they occasionally grew on top of each other in multilayered structures. This is in line with the manufacturer’s description of the cell line and conforms to previous reports in which the cells were cultured on PDL, plastic, or glass surfaces 37 . However, in the L511 and L521 coated wells, the cells continued to grow as monolayers, also toward confluency, which suggests more efficient adhesion to the substrate (Figure 1A).…”
Section: Resultssupporting
confidence: 91%
“…These cells are often used as a surrogate for peripheral sensory neurons since they extend long neurites and differentiate into polarized cells after addition of nerve growth factor and/or dbcAMP 37,55–58 . Moreover, differentiated ND7/23 cells express sensory neuron markers such as TrkA, Substance P, and CGRP, 37 which attest to their suitability for in vitro studies of peripheral nerve regeneration. We included several control substrates in order to benchmark the performance of NT2RepCT and VN‐NT2RepCT matrices, that is, PDL as it is the recommended substrate for ND7/23, L111, and L511 that have been reported to be important ECM proteins for neurite sprouting of adult DRG in vitro 14 and L521 that is present at neuromuscular junctions 59,60 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, phenotypic changes of repair SCs mainly include dedifferentiation ( Jessen and Mirsky, 2019 ), secretion of neurotrophic factors ( Pandey and Mudgal, 2021 ), production of cytokines to recruit immune cells ( Qu et al, 2021 ), and changes in morphology ( Jessen and Mirsky, 2016 ). After nerve injury, it is shown that a large amount of TGF-β is secreted by macrophages ( Sulaiman and Gordon, 2009 ), SCs ( Li et al, 2015 ; Clements et al, 2017 ), fibroblasts ( Clements et al, 2017 ), and the neurons ( van Rossum et al, 2008 ; Li et al, 2015 ) at the site of injury ( Jeon and Huxlin, 2020 ). Meanwhile, the expression level of TGF-β receptor is significantly upregulated in SCs and neurons ( Fregnan et al, 2012 ).…”
Section: Role Of Transforming Growth Factor-β In Peripheral Nerve Reg...mentioning
confidence: 99%